2013
DOI: 10.1007/s13361-012-0549-x
|View full text |Cite
|
Sign up to set email alerts
|

Does Addition of NO2 to Carbon-Centered Radicals Yield RONO or RNO2? An Investigation Using Distonic Radical Ions

Abstract: Nitrogen dioxide is used as a "radical scavenger" to probe the position of carbon-centered radicals within complex radical ions in the gas phase. As with analogous neutral radical reactions, this addition results in formation of an [M + NO2](+) adduct, but the structural identity of this species remains ambiguous. Specifically, the question remains: do such adducts have a nitro-(RNO2) or nitrosoxy-(RONO) moiety, or are both isomers present in the adduct population? In order to elucidate the products of such re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Gas‐phase reaction of NO 2 with 4‐( N , N , N ‐trimethylammonium)‐phenyl radical cation. (from reference: Kirk et al, 2013). …”
Section: Imr Of Radical Ionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gas‐phase reaction of NO 2 with 4‐( N , N , N ‐trimethylammonium)‐phenyl radical cation. (from reference: Kirk et al, 2013). …”
Section: Imr Of Radical Ionsmentioning
confidence: 99%
“…Gas‐phase synthesis of N , N , N ‐trimethyl‐4‐nitrosoxybenzaminium (A‐ONO) cation. (from reference: Kirk et al, 2013). …”
Section: Imr Of Radical Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spin-trapped DEPMPO-NO 2 adduct can be clearly observed at 243 Ka nd is consistentw ith previousr eports by Astolfi for an oxygen centered adduct (see Supporting Information). [24] Additionale vi-Scheme1.Traditionally,nitroalkenes have been accessed through avariety of strategies (A, B), we have developedanew nitratingr eagent-strategy based on aS ET redox active scaffold (C, D). dence of an ostensibly,l ess-stable nitrogen centered NO 2 adduct is also observed.…”
Section: Introductionmentioning
confidence: 99%
“…When Ru(bpy) 3 (PF 6 ) 2 and N -nitrosuccinimide in acetonitrile were irradiated with blue LEDs in the presence of 5-diethoxyphosphoryl-5-methyl-1-pyrroline- n -oxide (DEPMPO), a signal corresponding to NO 2 -DEPMPO radical adduct ( g = 2.0095, a P = 46.797 G, a N = 12.216 G, a H = 9.587 G, a H = 0.466 G, a H = 0.196 G) was clearly recorded by EPR and is consistent with previous literature reports. 7,17 However, in the absence of visible-light irradiation, the same reaction mixture of Ru(bpy) 3 (PF 6 ) 2 , DEPMPO, and N -nitrosuccinimide was found to be EPR silent. These experimental results confirmed that the NO 2 -radical was involved in the reaction system.…”
mentioning
confidence: 98%